Report of the Coir Enquiry Committee Parts I & II - Planning Commission (Planning Commission, 1958)
The Committee set out the questions for investigation, and issued a questionnaire to persons and organisations interested in the Coir Industry including Members of Parliament and Members of the Assembly in States where cocoanut was largely grown.
Government of India Try of Commerce & Industry
Government of India Try of Commerce & Industry